2016
DOI: 10.1038/ncomms12972
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and TOR signal in parallel through FOXO and S6K to promote epithelial wound healing

Abstract: The TOR and Insulin/IGF signalling (IIS) network controls growth, metabolism and ageing. Although reducing TOR or insulin signalling can be beneficial for ageing, it can be detrimental for wound healing, but the reasons for this difference are unknown. Here we show that IIS is activated in the cells surrounding an epidermal wound in Drosophila melanogaster larvae, resulting in PI3K activation and redistribution of the transcription factor FOXO. Insulin and TOR signalling are independently necessary for normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 70 publications
(100 reference statements)
3
91
0
Order By: Relevance
“…The transgenic tools like Gal4 drivers, fluorescently tagged proteins and other markers, which were originally developed and established for studies in embryos can also be used for larvae. In addition, larvae are resilient to heat-shock or UV irradiation, the methods used to induce mosaic clones and to control temperature sensitive protein function and optogenetic tools 34,[36][37][38] .…”
Section: Advantages Of Drosophila Larvae As a Model Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…The transgenic tools like Gal4 drivers, fluorescently tagged proteins and other markers, which were originally developed and established for studies in embryos can also be used for larvae. In addition, larvae are resilient to heat-shock or UV irradiation, the methods used to induce mosaic clones and to control temperature sensitive protein function and optogenetic tools 34,[36][37][38] .…”
Section: Advantages Of Drosophila Larvae As a Model Systemmentioning
confidence: 99%
“…Finally, it is easy to treat larvae with drugs, such as rapamycin, chloroquine, bafilomycin A1, wormatin, blebbistatin and many others, which can simply be administered by including them in the food 34,[57][58][59] . The larva therefore represents an attractive in vivo model both for fundamental and medically relevant questions.…”
Section: Advantages Of Drosophila Larvae As a Model Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The link between nutrition control and early regeneration has been examined by Maria Leptin (University of Cologne and the European Molecular Biology Laboratory, Germany). She showed that signalling through the insulin receptor (InR) and TOR is necessary for epithelial organization during wound healing in Drosophila (Kakanj et al, 2016). The insulin pathway activates Pi3K and FOXO, whereas the TOR pathway operates through the Atg1/Atg13 autophagy machinery.…”
Section: Insulin Signalling In Regeneration and Plasticitymentioning
confidence: 99%